Aktualisasi Nilai-nilai Pendidikan Islam dalam Membentuk Pola Hidup Sederhana di Madin Al-Isnaini Montong Wasi - Sapril NM (LP2M STIT Palapa Nusantara, 2016)
Research conducted by the author are included in the descriptive study. In the process of data collection, the author uses the method of observation, interview and documentation. Data analysis in this research using qualitative descriptive analysis, namely in the form of data written and interviews from a variety of key informants or sources of information on observed behavior, so with that, the author seeks to conduct descriptive research thoroughly about the actual situation happen.